Case Report: Synchronous cervical, gastric and rectal metastases in occult breast cancer - Deng, Ruoying; Meng, Ze; Li, Qiang; Wang, Yarong; Lan, Yuyun; Liu, Yao; Liu, Yibing (Frontiers in Oncology, 2025)
Occult breast cancer (OBC) is characterized as a breast carcinoma that remains undetectable through imaging modalities. OBC is a rare condition, accounting for only 0.3%-1.0% of all breast cancers, and is often clinically associated with metastases to the axillary and cervical lymph nodes. Metastasis of occult primary breast cancer to the cervix, stomach, or rectum is exceptionally rare. Here, we report the case of a 64-year-old woman presenting with clinical symptoms of urinary urgency, frequency, severe rectal discomfort, and altered stool morphology. Ga68-positron emission tomography-computed tomography (Ga68-FAPI PET/CT) identified diffuse tumor-associated fibrin expression within the gastric wall, while 18F-fluorodeoxyglucose PET/CT (18F-FDG PET/CT) revealed marked annular thickening of the rectal wall. Notably, imaging evaluations, including mammography, breast ultrasonography, and 18F-FDG PET/CT, failed to detect primary breast lesions. Histopathological examination and immunohistochemical analysis of biopsied cervical, gastric, and rectal lesions confirmed the diagnosis of OBC. Following six months of treatment with letrozole (1mg/day) in combination with dalpiciclib the patient demonstrated significant symptomatic relief, with remarkable reduction in the lesions located in the cervix, stomach, and rectum. This case represents the first documented instance of occult primary breast cancer with simultaneous metastases to the cervix, stomach, and rectum.